Respostas de Zeyheria tuberculosa (Vell) Bureau e Eremanthus erythropappus (DC.) MacLeish à aplicação de fertilizantes - Souza, Larissa Natasha de (2021)
In order to increase knowledge about mineral fertilization for forest species, two experiments were carried out with the species Zeyheria tuberculosa and Eremanthus erythropappus, both with high economic potential and still poorly studied in terms of silvicultural aspects. In the study carried out in chapter 1, under conditions of full sun in the field, with the species Zeyheria tuberculosa, popularly known as "ipê tabaco" or " ipê felpudo" different doses of NPK were applied, in four treatments, with four replications and five plants per installment. The following were tested: a treatment without N, P and K; one with the application only of P in the planting fertilization; one with the application of only N and K in topdressing; and one with the application of N, P and K. Over 20 months of height (H) and stem diameter (DC) measurements, no significant differences were observed between treatments. Factors such as low base saturation in the soil and low water availability may have influenced the growth of the species, it is important to continue the evaluations, since the differences in treatments can be expressed in older ages. In chapter 2 the experiment was carried out with the species Eremanthus erythropappus, popularly known as candeia. Under full sun conditions in the field, different doses of NPK were applied in six treatments, four being identical to those used for Zeyheria tuberculosa, adding two more treatments with increasing phosphorus dose, when the other nutrients were applied. Over 20 months of planting Eremanthus erythropappus seedlings, it was observed that maintenance fertilization, containing nitrogen and potassium, favored the growth in height (H) and stem diameter (DC). On the other hand, there was no response to the application of phosphorus in planting fertilization, even with increased doses, which makes candeia a peculiar species, since it does not present the same behavior as most forest species. Through these studies, knowledge about these species and the relationships between fertilizer doses and growth in the first years of planting has been expanded.